Assessing the integrity of CFRPs through nanomechanical mapping: the effect of CF surface modification - Koumoulos Elias P.; Kainourios Panagiotis; Charitidis Costas A. (MATEC Web of Conferences, 2018)
The purpose of this study is to assess the effect of CF surface modification in enhancement of the wetting properties of carbon fibers in order to improve the adhesion force between the fiber and the polymer matrix; for this, the integrity of CFRPs through nanomechanical mapping was evaluated. The surface of commercial carbon fibers was functionalized through cyclic voltammetry in aqueous electrolyte solutions of H2SO4, in the presence of acrylic acid, methacrylic acid, acrylonitrile and N-vinylpyrrolidone monomers. The produced surface modified carbon fibers were embedded in epoxy resin. Elastic modulus nanoindentation mapping was performed in order for elastic modulus to be calculated, as a qualitative assessment of fibre – matrix interaction. For this, a grid protocol was set up for the integrity assessment of CFRPs through nanomechanical mapping.